Adiabaticity Engineered Silicon Coupler With Design-Intended Splitting Ratio - Chih-Hsien Chen; Yu-Fang Lo; Guan-Xun Lu; Yung-Jr Hung; Shuo-Yen Tseng (IEEE Photonics Journal)
We design and experimentally demonstrate compact and robust adiabaticity engineered couplers (AECs) with design intended splitting ratios (SRs) for the silicon-on-insulator platform. Adiabatic couplers (ACs) with variable SRs can be designed by output waveguide width-differences. By analyzing the mode-evolution region of ACs, we redistribute the adiabaticity parameter by engineering the taper function to obtain fast quasiadiabatic evolution, thus reducing the device footprints. AECs with design-intended SRs exhibit broad bandwidth and robustness against fabrication variations. We experimentally demonstrate compact AECs with average SRs of 22%/78% and 15%/85% with mode-evolution lengths of 42 $μ$ m and 25 $μ$ m over a bandwidth of 70 nm, i.e., from 1500 to 1570 for the fundamental transverse electric (TE) mode.